1997
DOI: 10.1007/bf02263228
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability factors in depression: The facets of sociotropy and autonomy

Abstract: The Facets of Sociotropy-autonomy (Beck, 1983) describes a set of personality dimensions that relate to an individual's vulnerability to depression. Two recently developed scales, the Sociotropy-Autonomy Scale (Clark & Beck, 1991) (Clark & Beck, 1991). A factor analysis on all of the items of the two scales revealed a five-factor structure (two sociotropy, two autonomy, and one achievement factor). The relationships among depression, the five derived factors, and the original scales developed by Clark and Beck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 13 publications
(32 reference statements)
4
35
0
Order By: Relevance
“…These behavior patterns are also consistent with some past work on individuals with high levels of autonomy [e.g., Dunkley et al, 1997; , 1997]. Highly autonomous individuals have been reported to be more withdrawing than individuals who are low in autonomy [e.g., Bieling and Alden, 2001;Sato and McCann, 1997]. Bieling and Alden [2001] suggested that highly autonomous individuals tend to withdraw from social interaction if they feel that a high level of collaboration (i.e., relinquishing personal control) is required.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These behavior patterns are also consistent with some past work on individuals with high levels of autonomy [e.g., Dunkley et al, 1997; , 1997]. Highly autonomous individuals have been reported to be more withdrawing than individuals who are low in autonomy [e.g., Bieling and Alden, 2001;Sato and McCann, 1997]. Bieling and Alden [2001] suggested that highly autonomous individuals tend to withdraw from social interaction if they feel that a high level of collaboration (i.e., relinquishing personal control) is required.…”
Section: Discussionsupporting
confidence: 84%
“…The Solitude scale consists of 13 items, and the Independence scale, 17 items. Past research using the Sociotropy-Autonomy Scale has suggested that the Independence scale measure is unrelated to vulnerability to depression [Bieling et al, 2000;Clark et al, , 1997Sato, 1999, unpublished data;Sato and McCann, 1997. Due to these findings, our research focuses on the Solitude scale as a measure for autonomy.…”
Section: Methodsmentioning
confidence: 87%
“…satisfactory and supportive-sympathic) and negative (i.e. ccritical and procrustean and disciplinary) subscales of work relationships then its nature would be highly similar to the autonomy and sociotropic dimensions of people relationships in general settings and their effects in emotional problems like depression (35)(36)(37). Therefore, it speculated that work relationships included two distinct positive and negative factors and each of them has specific influences on emotional problems and stress in workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, people with sociotropy would like to put a high energy on their socially appropriate and prosocial competence. Investigations suggested a possible overlap between in these two dimensions, and presumed that individuals differ in relation to social relations and social knowledge (36,37). Therefore, this study speculates the significance of relationships in the workplace is a phenomenological issue and it influences the occurrence of stress, depression and anxiety in the workplace.…”
Section: Present Studymentioning
confidence: 99%
“…For example, both factor analyses of autonomy measures (e.g., Bagby, Parker, Joffe, Schuller, & Gilchrist, 1998;Bieling, Beck, & Brown, 2000;Clarke, Steer, Haslan, Beck, & Brown, 1997;Robins et al, 1994;Sato & McCann, 1997) and convergent correlations of the factors with other personality traits (Alden & Bieling, 1996;Bagby & Rector, 1998;Bagby et al, 2001;Cappeliez, 1993;Dunkley, Blankstein, & Flett, 1997;Gilbert & Reynolds, 1990;Ouimette, Klein, Anderson, Riso, & Lizardi, 1994;Mongrain, 1993;Zuroff, 1994) support the contention that the autonomous dimension may be further subdivided into social (withdrawal, disinterest), control (dogmatic, authoritarian), and achievement-relevant (perfectionistic striving, self-critical) factors. Recently, a number of researchers have began to utilize these distinctions in tests of depressive vulnerability, and the results have led some investigators to propose that the interpersonal-control aspects of autonomy may be the "key feature of the autonomous cognitive-personality style" (Mazure, Raghavan, Maciejewski, Jacobs, & Bruce, 2001, p. 222;Little & Garber, 2000;Nelson, Hammen, Daley, Burge, & Davila, 2001).…”
mentioning
confidence: 98%